A deletion spanning the promoter and first exon of the hair cycle‐specific ASIP transcript isoform in black and tan rabbits. (15th November 2019) - Letko, A.; Ammann, B.; Jagannathan, V.; Henkel, J.; Leuthard, F.; Schelling, C.; Carneiro, M.; Drögemüller, C.; Leeb, T.
Summary: Black and tan animals have tan‐coloured ventral body surfaces separated by sharp boundaries from black‐coloured dorsal body surfaces. In the a t mouse mutant, a retroviral 6 kb insertion located in the hair cycle‐specific promoter of the murine Asip gene encoding agouti signalling protein causes the black and tan phenotype. In rabbits, three ASIP alleles are thought to exist, including an a t allele causing a black and tan coat colour that closely resembles the mouse black and tan phenotype. The goal of our study was to identify the functional genetic variant causing the rabbit a t allele. We performed a WGS‐based comparative analysis of the ASIP gene in one black and tan and three wt agouti‐coloured rabbits. The analysis identified 75 a t ‐associated variants including an 11 kb deletion. The deletion is located in the region of the hair cycle‐specific ASIP promoter and thus in a region homologous to the site of the retroviral insertion causing the a t allele in mice. We observed perfect association of the genotypes at this deletion with the coat colour phenotype in 49 rabbits. The comparative analysis and the previous knowledge about the regulation of ASIP expression suggest that the 11 kb deletion is the most likely causative variant for the black and tan phenotype in rabbits.